HUBUNGAN KAUSALITAS ANTARA PENGELUARAN PEMERINTAH DAN PERTUMBUHAN EKONOMI DI PROVINSI KALIMANTAN BARAT - B01112048, Yuniarni (Jurnal Curvanomic, 2017)
Kata Kunci : Pengeluaran Pemerintah, Pertumbuhan EkonomiABSTRACTThe development of economic occurs because any process in increasing output per capita that continuously for long-term. The economic growth is one of indicator in construction development. The government expending is intervention tool to economic matter that the most effective. The more increasing of government expending, the more increasing of economic development will be. The purpose of this research is to know the relation between the causality of government expending and economic development in west Kalimantan during 1995-2014. Thai is combination of tome series data. The processed by using a computer software program economic views (E-views 8). Which is used the method of causality Granger. The result of this research is concluded that between the government expending and economic development do not have any relation causality. That is because all of variable in this research has been stationary and lag 3 is occurring by relation in one purpose. The testing was conducted at the level (ð›¼) 5% and the result score probability is smaller to significant credibility level (ð›¼) 5% to government expending with economic growth. Therefore, government expending is influence economic development.Keywords : government expending, economic development